The Degree of Availability of Common American Basic Standards (CCSSM) in the Mathematics Textbooks Developed for the High Basic Stage in Palestine - Al-deeb , Majed (Dirasat: Educational Sciences, 2021)
The study aims at determining the degree of availability of the Common Core State Standards (CCSSM) in the Palestinian Mathematics books. The study adopted the descriptive-analytical approach in order to describe the basic features of the collected data effectively. The two research tools applied in the study were (CCSSM) and the Content Analysis Card. The study sample consisted of all mathematics books for the upper basic stage (5-10) in Palestine, which includes (12) books - 6 books for the first part and 6 books for the second part. The results of the study showed a high level of the availability of the (CCSSM) in the 6 grades of the upper basic stage as a whole with a high degree of (79.04%). Moreover, the degree of availability of American standards was in the first place for the fifth-grade books with a high degree at a rate of (98.61%), followed by the second place for the books of the ninth grade with a high degree at a rate of (86.61%). The results also showed the books of the eighth grade come in third place with a high degree of (84.15%). The tenth-grade books come in fourth place with a high degree of (82.78%). The tenth grade is followed by seventh-grade books with a moderate degree of (65.00%) which is finally followed by the sixth-grade books with a moderate degree of (54.24%). The study recommended the necessity of developing and enriching mathematics books with functional activities associated with American standards.